Health risk of heavy metals in celosia argentea L. Grown on municipal Waste soils in Ibadan, Nigeria (2017)
This paper assessed the appropriateness of dumpsites in Urban and Peri-urban Agriculture (UPA). The bioaccumulation and potential heavy metal-toxicity risk of consuming Celosia argentea L. grown on four different dumpsites soils (Ajibode, Sasa, Moniya and Akinyele) and reference soil from University of Ibadan Training and Research Farm was also evaluated. The soil samples were analysed for Cd, Cu, Fe, Ni, Pb and Zn using Atomic Absorption Spectrophotometry (AAS). None of the heavy metals was above European Union (EU) guidelines for safe limits of soil heavy metals in agricultural soils. The Pollution Load Indices (PLIs) were mostly>l, which indicated the deterioration of the sites quality in relation to specific heavy metal(s); ranging between 0.92-13.1. The daily intake of heavy metals (DIMs) and Health Risk Indices (HRIs) were evaluated based on the maximum recommended limit (MRL) by WHO/FAO standard. Most of the heavy metals were significantly low, but lead (Pb) was above the MRL. HRIs were between 0.02-0.03, 0.070.11, 0.61-4.43 and 0.03-0.04 for Cu, Fe, Pb and Zn respectively, Ni was found to have insignificant level (<0.0001). Only lead (Pb) has potential health risk (HRI>1) in all the sites except Moniya (0.61; HRI<1, safe) which might be as a result of vehicular exhaust and type of waste disposed. Soil test to ascertain the pollution status and crop type to produce should precede cropping have been recommended